1990
DOI: 10.1007/bf01313271
|View full text |Cite
|
Sign up to set email alerts
|

Copper uptake by the sea anemoneAnemonia viridis and the role of zooxanthellae in metal regulation

Abstract: Abstract-, Anemonia viridis (Forsk/il) were collected from south-west Scotland and south-west England in October 1988. When exposed to 0.05 and 0.2 mg 1 -a copper in sea water, anemones did not take up the metal in proportion to external concentrations. Results suggested that A. viridis regulated copper by expelling symbiotic algae (or zooxanthellae) which were shown to accumulate copper. The use of aposymbiotic (non-zooxanthellate) anemones in similar metaluptake experiments indicated that other mechanisms ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 20 publications
9
40
0
Order By: Relevance
“…17 This theory is supported by the fact that aposymbiotic, or azooxathellate, anemone accumulate copper at a faster rate as compared with symbiotic anemone. 17 Alternatively, zooxanthellae expulsion in the sunburst anemone presented here may be a nonspecific response due in part to gastrodermal necrosis/ulceration. Cyanide exposure in cnidaria reportedly causes several morphologic changes to zooxanthellae, including swelling, increased mitotic rate, abnormal expulsion into the gastrovascular cavity, and partial bleaching.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…17 This theory is supported by the fact that aposymbiotic, or azooxathellate, anemone accumulate copper at a faster rate as compared with symbiotic anemone. 17 Alternatively, zooxanthellae expulsion in the sunburst anemone presented here may be a nonspecific response due in part to gastrodermal necrosis/ulceration. Cyanide exposure in cnidaria reportedly causes several morphologic changes to zooxanthellae, including swelling, increased mitotic rate, abnormal expulsion into the gastrovascular cavity, and partial bleaching.…”
Section: Discussionsupporting
confidence: 51%
“…17 Studies have demonstrated that zooxanthellae uptake excessive environmental copper, thereby buffering host anemone from the effects of copper accumulation. 17,26 Expulsion of zooxanthellae may be a regulatory response to increased copper storage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acropora formosa exposed to > 20 µg Cu l -1 for 48 h had significantly fewer symbiotic dinoflagellates than the respective control corals, and loss of symbiotic dinoflagellates from A. formosa (measured by examining the incubation water) was detected at concentrations as low as 5 and 10 µg Cu l -1 (Jones 1997). Loss of symbiotic dinoflagellates has been reported in sea anemones Anemonia viridis exposed to 200 µg Cu l -1 for 3 to 5 d (Harland & Ngrano 1990), and even from clams Tridacna crocea exposed to 60 µg Cu l -1 for >10 d (Duquesne & Coll 1995).…”
Section: Copper-induced Bleaching Of Coralmentioning
confidence: 97%